Maximum inferior vena cava diameter predicts post-induction hypotension in hypertensive patients undergoing non-cardiac surgery under general anesthesia: A prospective cohort study - Zhang, Hanying; Gao, Hongguang; Xiang, Yuanjun; Li, Junxiang (Frontiers in Cardiovascular Medicine, 2022)
Background: Inferior vena cava (IVC) ultrasonography is a reliable variable that predicts post-induction hypotension (PIH) in patients undergoing surgery under general anesthesia. In patients with hypertension, however, the predictive performance of ultrasound IVC measurements needs further exploration. Methods: This is a prospective cohort study. Adult patients with existing hypertension scheduled to undergo non-cardiac surgery under general anesthesia were eligible. Abdominal ultrasound examination was conducted immediately prior to anesthesia induction (0.03 mg kg-1 midazolam, 0.3 mg kg-1 etomidate, 0.4 µg kg-1 sufentanil and 0.6 mg kg-1 rocuronium). IVC-CI was calculated as (dIVCmax - dIVCmin)/dIVCmax, where dIVCmax and dIVCmin represent the maximum and minimum IVC diameter at the end expiration and inspiration, respectively. PIH was defined as a reduction of mean arterial pressure (MAP) by >30% of the baseline or to <60 mmHg within 10 minutes after endotracheal intubation. Diagnostic performance of IVC-CI, dIVCmax and dIVCmin in predicting PIH was also examined in a group of normotensive patients receiving non-cardiac surgery under the same anesthesia protocol. Results: A total of 51 hypertensive patients (61 ±13 years of age, 31 women) and 52 normotensive patients (42 ±13 years of age, 35 women) were included in the final analysis. PIH occurred in 33 (64.7%) hypertensive patients and 19 (36.5%) normotensive patients. In normotensive patients, the area under the receiver operating curve (AUC) in predicting PIH was 0.896 (95% confidence interval [CI]: 0.804-0.987) for IVC-CI, 0.770 (95% CI: 0.633- 0.908) for dIVCmax and 0.868 (95% CI: 0.773-0.963) for dIVCmin. In hypertensive patients, the AUC in predicting PIH was 0.523 (95% CI: 0.354- 0.691) for IVC-CI, 0.752 (95% CI: 0.621- 0.883) for dIVCmax, and 0.715 (95% CI: 0.571- 0.858) for dIVCmin. At the optimal cutoff (1.24 cm), dIVCmax had 54.5% (18/33) sensitivity and 94.4% (17/18) specificity. Conclusions: In hypertensive patients, IVC-CI is not suitable in predicting PIH, and dIVCmax is an alternative measure with promising performance.